BRCA1 and BRCA2 mutations in Japanese patients with ovarian, fallopian tube, and primary peritoneal cancer. Issue 1 (6th October 2015) - Sakamoto, Ikuko; Hirotsu, Yosuke; Nakagomi, Hiroshi; Ouchi, Hidetaka; Ikegami, Atsushi; Teramoto, Katsuhiro; Amemiya, Kenji; Mochizuki, Hitoshi; Omata, Masao
Abstract : BACKGROUND: The contribution of BRCA1 and BRCA2 to ovarian cancer in Japanese patients is still unclear. This study investigated the frequency of germline mutations in BRCA1 / 2 in Japanese patients with ovarian, peritoneal, or fallopian tube cancer, regardless of their family histories, which were suggestive of hereditary breast and ovarian cancer. METHODS: Ninety‐five unselected women with ovarian cancer who were seen from 2013 to 2015 at Yamanashi Prefectural Central Hospital were enrolled. Analyses of BRCA1 / 2 gene mutations were performed with next‐generation sequencing. RESULTS: Twelve of the 95 patients (12.6%), including 5 in the BRCA1 (5.3%) and 7 in the BRCA2 (7.4%), had deleterious mutations. Among the 36 cases with a family history, 6 (16.7%) were found to carry mutations in BRCA1 and BRCA2 . Notably, 6 of the 59 cases (10.2%) without a family history also had BRCA1 / 2 germline mutations. There was no statistical difference between the 2 groups ( P = .36). The presence of mutations and their clinical relevance were studied. Mutation carriers were diagnosed at advanced stages (100% of positive cases among stage III or IV cases) and had poor prognostic histological subtypes (100% of positive cases had high‐grade serous adenocarcinomas). CONCLUSIONS: In this unselected Japanese population, approximately 13% of the cases with ovarian cancer appeared to be associated with an inherited risk, regardless of a family history. This finding indicates that BRCA1 / 2 genetic testing should be performed for all patients with ovarian cancers. Cancer 2016;122:84–90. © 2015 American Cancer Society . Abstract : Approximately 13% of cases (12 of 95 patients) with ovarian cancer appear to be associated with an inherited risk, regardless of a family history. This finding indicates that BRCA1 / 2 genetic testing should be performed for all patients with ovarian cancer.